POLICY NETWORK THEORY IN THE STUDY OF MODERN POLITICAL PROCESSES - Kozyretska, Daryna (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
In the modern globalized world, political processes increasingly occur as a result of interactions between individual actors who form networks. Contemporary political processes are examined through the lens of Policy Network Theory. This theory elucidates the essence and content of Policy Network Theory itself, highlighting the importance of studying networks in political processes and the value of network theory as a subfield of political science for developing new concepts to analyze and explain diverse political phenomena and current trends. It is noted that politicians, business structures, and civil society organizations, by uniting based on shared interests, can influence the political decision-making process no less effectively than state institutions. Networks in political processes are characterized by decentralization, close interaction, and an ever-changing structure in which resources, including financial assets, information, or simply ideas, are constantly exchanged. An illustrative example of network formation in the political process in Ukraine is the «Servant of the People» Political party. Founded on the eve of the parliamentary elections, this leading party created a network of a new political elite whose members had no prior experience in politics, but included industry experts, activists, business representatives, and cultural figures. By adopting a decentralized approach to communication and organizing support at the regional level, the party managed to build a nationwide network in a short period of time. This example illustrates how a political party can operate within the network model, uniting different social groups around a common goal and using horizontal links to effectively disseminate its ideas and implement initiatives. The study of works from the German and British schools of social network analysis leads to the conclusion that traditional approaches to analyzing political processes and explaining the dynamics of modern politics are insufficient. These approaches primarily focus on studying rules and norms, the development of structures, and institutional interactions, while overlooking more complex interconnections and their causality.It is proposed to view the foundations of Policy Network Theory as a new approach to understanding political processes, emphasizing the critical role of connections and interdependencies among various political actors. The evolution of Policy Network Theory is traced, beginning in the 1970s with the emergence of the neo-institutional approach, and its importance for studying contemporary political processes in the context of modern transformations is substantiated.It is suggested that political power should be viewed not as a hierarchical structure but as a network, where each node (e.g., state authorities, intergovernmental organizations, business corporations, or civil society associations) can influence the overall outcome of policy. It is suggested to adopt new terminology, previously unused in Ukrainian political science, for studying networks of political actors.The relevance of Policy Network Theory is emphasized, and its application in future research is recommended as a tool that allows for the consideration of the broadest range of factors influencing policymaking.